2020
DOI: 10.1177/1948550619896168
|View full text |Cite
|
Sign up to set email alerts
|

Disliked but Free to Speak: Cognitive Ability Is Related to Supporting Freedom of Speech for Groups Across the Ideological Spectrum

Abstract: Freedom of speech for all citizens is often considered as a cornerstone of democratic societies. In three studies, we examined the relationship between cognitive ability and support for freedom of speech for a variety of social groups across the ideological spectrum ( N 1 varies between 1,373 and 18,719, N 2 = 298, N 3 = 395). Corroborating our theoretical expectations, although cognitive ability was related to more affective prejudice toward relatively conservative groups and less affective prejudice toward r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…Those who are better able to think carefully about things are more likely to reflect on the different pros and cons and arrive at a balanced conclusion. Research has shown that despite one’s positive or negative group feelings, people with a higher cognitive ability are more in favor of tolerating speech for all social-ideological groups (De Keersmaecker et al, 2021).…”
Section: Individual Differencesmentioning
confidence: 99%
“…Those who are better able to think carefully about things are more likely to reflect on the different pros and cons and arrive at a balanced conclusion. Research has shown that despite one’s positive or negative group feelings, people with a higher cognitive ability are more in favor of tolerating speech for all social-ideological groups (De Keersmaecker et al, 2021).…”
Section: Individual Differencesmentioning
confidence: 99%
“…Specifically, while De Keersmaecker et al. (2021) confirmed prior observations that higher intelligence was associated with liking some groups and disliking others, they found intelligence nevertheless positively predicted the endorsement of freedom of speech for all groups, even those for whom intelligence negatively predicted affect. This is certainly suggestive of a positive role for intelligence in predicting tolerance, but unfortunately De Keersmaecker et al.…”
Section: Introductionmentioning
confidence: 68%
“…This is certainly suggestive of a positive role for intelligence in predicting tolerance, but unfortunately De Keersmaecker et al. 's (2021) analyses were limited by the second and third considerations noted above. That is, when analyzing free speech endorsement, De Keersmaecker et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Интеллектуальная скромность снижает эффект воспринимаемой непохожести аутгруппы на предрассудки по отношению к ней [6]. Связь когнитивных способностей и поддержки свободы слова политических оппонентов опосредована интеллектуальной скромностью [17]. Респонденты с низким уровнем интеллектуальной скромности более склонны принижать интеллектуальные способности и негативно отзываться о моральном облике своих оппонентов, в меньшей степени готовы дружить с ними, в том числе «френдиться» в социальных сетях [34].…”
Section: интеллектуальная скромность потребность в когнитивной завершенности и радикализацияunclassified